Influence of E-Procurement on Peformance of Food and Beverage Firms in Nairobi County, Kenya - Otieno, Samuel Ouma; Achuora, John (International Journal of Supply Chain and Logistics, 2018)
Purpose: The main purpose of this study was to examine the influence of e-procurement on performance of food and beverage firms in Nairobi County.Methodology:The study employed a cross sectional descriptive census research design.The study conducted a census since the number of the firms is less than 200, which is a rule of the thumb. Primary data was collected through a questionnaire which was piloted for reliability and validity. The unit of observation was the heads of procurement due to their knowledge on the subject of the study and the unit of analysis was food and beverages firms. The study used convenience sampling to sample the unit of observation.Descriptive statistics including frequencies, percentages, means and standard deviations was used to capture the characteristics of the variables and inferential statistics(correlation and regression analysis)were used to analyze the relationships between the dependent and the independent variables.Results:First, in regard to electronic payments, the regression coefficients of the study show that it has a significant influence of 0.166 on performance of food and beverage firms.Second in regard to electronic contracting, the regression coefficients of the study show that it has a significant influence of 0.138 on performance of food and beverage firms.With regard to electronic mailing, the regression coefficients of the study show that it has a significant influence of 0.119 on performance of food and beverage firms.Lastly, in regard to the fourth objective, the regression coefficients of the study show that it has a significant influence of 0.09 on performance of food and beverage firms. Conclusion and Policy Recommendation:The findings of the study concluded that electronic payments, electronic contracting, electronic mailing and electronic ordering have a positive relationship with performance of food and beverage firms.The study recommends that firms should embrace e-procurement so as to improve performance and further researches should to be carried out in other institutions to find out if the same results can be obtained
Keywords: Electronic Payments; Electronic Contracting; Electronic Mailing; Electronic Ordering